PEDAGOGICAL FOUNDATIONS OF DEVELOPING THE INNOVATIVE COMPETENCE OF PRIMARY SCHOOL TEACHERS (Journal of Universal Science Research, 2026)
. The article highlights the issues of developing teachers' innovative competence, as well as the theoretical and practical aspects of introducing innovations into the modern pedagogical process. The readiness of teachers for innovative activity, the importance of professional development, and the impact of using digital technologies on the quality of education are analyzed.